Analisis Sektor Unggulan Untuk Pembangunan Ekonomi Di Kabupaten Pesawaran - Weliza Weliza; Agus Hudoyo; Muhammad Irfan Affandi (Journal of Food System & Agribusiness, 2021)
This study aimed to analyze the leading sectors for economic development in Pesawaran Regency. The data used is secondary data, namely the Gross Domestic Regional Products (GDRP) and the Input-Output Table. These data were analyzed using the Location Quotient (LQ) method, Shift-share analysis, and Input-Output analysis. The results of the analysis revealed that the leading economic sectors that drive the economy in Pesawaran Regency were wholesale and retail trade; wood industry, goods from wood and cork and woven goods from bamboo, rattan and the like; horticulture; construction; plantation; and fisheries. Keywords: Location Quotient, Shift-Share Input-Output, Leading Sector.